Relationship of Platelet Reactivity With Bleeding Outcomes During Long‐Term Treatment With Dual Antiplatelet Therapy for Medically Managed Patients With Non‐ST‐Segment Elevation Acute Coronary Syndromes. Issue 11 (November 2016) - Cornel, Jan H.; Ohman, E. Magnus; Neely, Benjamin; Jakubowski, Joseph A.; Bhatt, Deepak L.; White, Harvey D.; Ardissino, Diego; Fox, Keith A.A.; Prabhakaran, Dorairaj; Armstrong, Paul W.; Erlinge, David; Tantry, Udaya S.; et al.
Abstract : Background: The relationship between "on‐treatment" low platelet reactivity and longitudinal risks of major bleeding dual antiplatelet therapy following acute coronary syndromes remains uncertain, especially for patients who do not undergo percutaneous coronary intervention. Methods and Results: We analyzed 2428 medically managed acute coronary syndromes patients from the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes (TRILOGY ACS) trial who had serial platelet reactivity measurements (P2Y12 reaction units; PRUs) and were randomized to aspirin+prasugrel versus aspirin+clopidogrel for up to 30 months. Contal's method was used to determine whether a cut point for steady‐state PRU values could distinguish high versus low bleeding risk using 2‐level composites: Global Use of Strategies to Open Occluded Coronary Arteries (GUSTO) severe/life‐threatening or moderate bleeding unrelated to coronary artery bypass grafting (CABG) and non‐CABG Thrombolysis In Myocardial Infarction (TIMI) major or minor bleeding. Exploratory analyses used 3‐level composites that incorporated mild and minimal GUSTO and TIMI events. Continuous measures of PRUs (per 10‐unit decrease) were not independently associated with the 2‐level GUSTO (adjusted hazard ratio [HR], 1.01; 95% CI, 0.96–1.06) or TIMI composites (1.02; 0.98–1.07). Furthermore, no PRU cut point could significantly distinguish bleeding risk using the 2‐level composites. However, the PRU cut point of 75 differentiated bleeding risk with the 3‐level composites of GUSTO (26.5% vs 12.6%; adjusted HR, 2.28; 95% CI, 1.77–2.94; P <0.001) and TIMI bleeding events (25.9% vs 12.2%; adjusted HR, 2.30; 95% CI, 1.78–2.97; P <0.001). Conclusions: Among medically managed non‐ST‐segment elevation acute coronary syndromes patients receiving prolonged dual antiplatelet therapy, PRU values were not significantly associated with the long‐term risk of major bleeding events, suggesting that low on‐treatment platelet reactivity does not independently predict serious bleeding risk. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00699998.